White matter hyperintensities in relation to cognition in HIV-infected men with sustained suppressed viral load on combination antiretroviral therapy. (24th September 2016) - Su, Tanja; Wit, Ferdinand W.N.M.; Caan, Matthan W.A.; Schouten, Judith; Prins, Maria; Geurtsen, Gert J.; Cole, James H.; Sharp, David J.; Richard, Edo; Reneman, Liesbeth; Portegies, Peter; Reiss, Peter; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: The objective of this study was to assess whether HIV-infected patients on long-term successful combination antiretroviral therapy (cART) have more extensive white matter hyperintensities (WMH) of presumed vascular origin compared with uninfected controls and whether these intensities are associated with cognitive impairment. Furthermore, we explored potential determinants of increased WMH load long-term suppressed HIV infection. Design: A cross-sectional comparison of WMH in an observational cohort. Methods: Clinical, cognitive, and MRI data were collected from 103 middle-aged, aviremic HIV-infected men on cART, and 70 HIV-uninfected, otherwise similar controls. In the MRI data, WMH load was quantified by automated approaches and qualitatively reviewed by an experienced neuroradiologist using the Fazekas scale. Results: HIV-infected men had an increased WMH load. Among HIV-infected patients, increased WMH load was independently associated with older age, higher DBP, higher D-dimer levels, and longer time spent with a CD4 + cell count below 500 cells/μl. HIV-associated cognitive deficits were associated with increased WMH load. Conclusions: WMH are more extensive and associated with cognitive deficits in middle-aged, aviremic cART-treated HIV-infected men. The extent of WMH load was associated with both cardiovascular risk factors and past immune deficiency. As cognitive impairment in these same patients is also associated with these risk factors, this may suggest that in the setting of HIV, WMH, and cognitive deficits share a common cause. This supports the importance of optimizing cardiovascular risk management, and early, effective treatment of HIV infection.